The interstellar medium in Andromeda's dwarf spheroidal galaxies: II. Multi-phase gas content and ISM conditions - Looze, Ilse de; Cormier, Diane (Arxiv, 2016)
We make an inventory of the interstellar medium material in three low-metallicity dwarf spheroidal galaxies of the Local Group (NGC147, NGC185 and NGC205). Ancillary HI, CO, Spitzer IRS spectra, Hα and X-ray observations are combined to trace the atomic, cold and warm molecular, ionised and hot gas phases. We present new Nobeyama CO(1-0) observations and Herschel SPIRE FTS [CI] observations of NGC205 to revise its molecular gas content. We derive total gas masses of M_gas = 1.9-5.5x10^5 Msun for NGC185 and M_gas = 8.6-25.0x10^5 Msun for NGC205. Non-detections combine to an upper limit on the gas mass of M_gas =< 0.3-2.2x10^5 Msun for NGC147. The observed gas reservoirs are significantly lower compared to the expected gas masses based on a simple closed-box model that accounts for the gas mass returned by planetary nebulae and supernovae. The gas-to-dust mass ratios GDR~37-107 and GDR~48-139 are also considerably lower compared to the expected GDR~370 and GDR~520 for the low metal abundances in NGC 185 (0.36 Zsun) and NGC205 (0.25 Zsun), respectively. To simultaneously account for the gas deficiency and low gas-to-dust ratios, we require an efficient removal of a large gas fraction and a longer dust survival time (~1.6 Gyr). We believe that efficient galactic winds (combined with heating of gas to sufficiently high temperatures in order for it to escape from the galaxy) and/or environmental interactions with neighbouring galaxies are responsible for the gas removal from NGC147, NGC185 and NGC205.